2018
DOI: 10.1039/c8nr02527d
|View full text |Cite
|
Sign up to set email alerts
|

High electrocatalytic performance inspired by crystalline/amorphous interface in PtPb nanoplate

Abstract: Nanoscale PtPb catalysts with core-shell structure have been actively explored in recent years owing to their outstanding catalytic activity. We report on a new class of PtPb nanoplate (NP) catalyst with a novel structure realized by ion irradiation modification, which contains an interface formed by a crystalline phase and an amorphous phase simultaneously in an annular state. Significantly, the PtPb NP with the new structure shows superior catalytic activity towards the methanol oxidation reaction (MOR). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…Second, in comparison to both commercial Pd/C and Pd black, the more negative onset potentials of FAO (Figure c) and adsorbed OH ad (Figure S7, Supporting Information) for P‐Pd nanosheets might be related to the interfaces between amorphous and crystalline regions, which activate the CH and OH bonds and enhance the adsorption energy of OH ad to oxidize CO‐like intermediates, resulting in fast electrode kinetics for FAO. The property of the interfaces can also be found in previously reported literature according to the density functional theory calculations . Finally, their crosslinked nanosheet structure and rich perforations could contribute to reduce R ct for electron transport and fast mass transfer, respectively, which are consist with the analysis of AC impedances in Figure e.…”
supporting
confidence: 65%
“…Second, in comparison to both commercial Pd/C and Pd black, the more negative onset potentials of FAO (Figure c) and adsorbed OH ad (Figure S7, Supporting Information) for P‐Pd nanosheets might be related to the interfaces between amorphous and crystalline regions, which activate the CH and OH bonds and enhance the adsorption energy of OH ad to oxidize CO‐like intermediates, resulting in fast electrode kinetics for FAO. The property of the interfaces can also be found in previously reported literature according to the density functional theory calculations . Finally, their crosslinked nanosheet structure and rich perforations could contribute to reduce R ct for electron transport and fast mass transfer, respectively, which are consist with the analysis of AC impedances in Figure e.…”
supporting
confidence: 65%
“…In addition, these materials are either heteromaterials, in which the crystalline and amorphous areas are made of different chemical compositions, such as CuS (crystalline)/Pd‐Cu‐S (amorphous) [ 12,13 ] and Co (crystalline)/Co 3 O 4 (amorphous), [ 14 ] or homomaterials with the random distribution of the crystalline and amorphous areas, such as PtPb, [ 15 ] Pd, [ 11 ] and PdCu. [ 10 ] Furthermore, additional post‐treatment processes, such as ion irradiation treatment of the presynthesized crystalline nanoplates, [ 15,16 ] were required to obtain some of the heterostructures. Therefore, it still remains a great challenge to construct well‐defined core–shell crystalline@amorphous heterostructured nanomaterials with the same chemical components.…”
Section: Figurementioning
confidence: 99%
“…First, the coexistence of crystalline and amorphous structures in c ‐Pd‐Ni‐P@ a ‐Pd‐Ni‐P nanoplates benefits the formation of low‐coordination atoms, giving rise to the change of electron band structure of the Pd atoms and the enhancement in electrocatalytic activity. [ 15,16,30 ] Second, it has been demonstrated that the incorporation of oxophilic metal, such as Ni, into the Pd‐based catalysts could benefit the generation of *OH and thus enhance the catalytic activity in EOR. [ 20 ] During the EOR process, the Pd atoms generally promote the dehydrogenation of ethanol to form *CH 3 CO, which can combine with the *OH formed on Ni atoms to generate CH 3 COOH that further becomes CH 3 COO − after the reaction with OH − in the alkaline electrolyte.…”
Section: Figurementioning
confidence: 99%
“…Such oxygenated species can promote the further oxidation of CO ads , and then remove them from Pt sites, which substantially enhance the catalytic properties of these three Pd 3 Pb/Pt n Pb nanocubes toward MOR. As such, the adsorption energy of CO on Pt‐based electrocatalysts is a critical descriptor of the intrinsic activity for MOR . In order to deeply understand the difference in MOR activity of three Pd 3 Pb/Pt n Pb nanocubes, the adsorption energies of CO on fcc‐structured Pt(111), fcc‐structured Pt x Pb(111), and hexagonal‐structured PtPb(0001) were obtained by the density functional theory (DFT) calculations.…”
mentioning
confidence: 99%